Pentaho data integration 4 cookbook : over 70 recipes to solve ETL problems using Pentaho Kettle - Sergio Pulvirenti, Adrián (Quick answers to common problems., 2011)
This book has step-by-step instructions to solve data manipulation problems using PDI in the form of recipes. It has plenty of well-organized tips, screenshots, tables, and examples to aid quick and easy understanding. If you are a software developer or anyone involved or interested in developing ETL solutions, or in general, doing any kind of data manipulation, this book is for you. It does not cover PDI basics, SQL basics, or database concepts. You are expected to have a basic understanding of the PDI tool, SQL language, and databases.